2019
DOI: 10.1111/jch.13706
|View full text |Cite
|
Sign up to set email alerts
|

Stage 1 hypertension defined by the 2017 ACC/AHA guideline predicts future cardiovascular events in elderly Chinese individuals

Abstract: The 2017 American College of Cardiology and American Heart Association (ACC/AHA) hypertension guideline updated stage 1 hypertension defined as systolic blood pressure (SBP) of 130‐139 mm Hg or diastolic blood pressure (DBP) of 80‐89 mm Hg. However, the impact of 1 hypertension that affects future cardiovascular risk remains unclear among older adults in rural China. The prospective cohort study included 7503 adults aged ≥60 years with complete data and no cardiovascular disease (CVD) at baseline. Follow‐up fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…In China, most cardiovascular specialists have suggested that the threshold BP of the 2017 ACC/AHA hypertension guideline may not be adaptable currently in China. 6 Although prospective cohort studies from China and other countries have shown a positive association of 130-139/80-89 mm Hg with the onset of subsequent cardiovascular diseases, [22][23][24] whether or not the new definition of hypertension will improve the control of hypertension and reduce the risk of cardiovascular disease without a substantial increase of cost is still controversial. 25,26 Limitations should be considered in light of these results.…”
Section: Discussionmentioning
confidence: 99%
“…In China, most cardiovascular specialists have suggested that the threshold BP of the 2017 ACC/AHA hypertension guideline may not be adaptable currently in China. 6 Although prospective cohort studies from China and other countries have shown a positive association of 130-139/80-89 mm Hg with the onset of subsequent cardiovascular diseases, [22][23][24] whether or not the new definition of hypertension will improve the control of hypertension and reduce the risk of cardiovascular disease without a substantial increase of cost is still controversial. 25,26 Limitations should be considered in light of these results.…”
Section: Discussionmentioning
confidence: 99%